Rational Emotive Behavior Therapy (REBT): Philosophical and Conceptual Foundations and Implementation in Guidance and Counseling Practice - Riza Melinda; Budi Purwoko; Bakhrudin All Habsy (CV. Publikasi Indonesia, 2026)
Rational Emotive Behavior Counseling (REBC) is a cognitive-behavioral counseling approach developed by Albert Ellis and focuses on the role of irrational beliefs in causing emotional and behavioral disorders. This article aims to comprehensively examine the philosophical foundation, conceptual structure, intervention techniques, role of counselors, counseling stages, and the relevance of REBC in contemporary guidance and counseling practice. This study was based on the main literature on counseling theories from Capuzzi & Gross (2007), Corey (2009), Nelson-Jones (2001), Parrott (2003), Prochaska & Norcross (2007), Seligman (2006), and Sharf (2004), and supported by various national journals indexed by SINTA 4 or more. The results of the study show that REBC is effective in treating anxiety, depression, academic stress, maladaptive behavior, and self-adjustment problems in various settings, including educational and clinical. This approach emphasizes cognitive restructuring through the ABCDE model, active dispute, and systematic behavioral training. This article concludes that REBC is highly relevant to be applied in guidance and counseling services in Indonesia, especially in the context of higher education and schools.